KARAKTERISTIK RAGAM KULTIVAR KELAPA (Cocos nucifera L.) YANG DIGUNAKAN SEBAGAI BAHAN UPAKARA PADUDUSAN ALIT DI BALI - Eniek Kriswiyanti (Research Center for Biology-Indonesian Institute of Sciences, 2012)
Exploration have been conducted to determine characters variation of coconut (Cocos nucifera L.) usually used in Upakara Padudusan Alit ceremonial by Balinese people, covering coconut plantation areas in each regency (kabupaten) of Bali.The characterization is based on measurement and observation of parts of plant according to ”Descriptors for Coconut” (IBPGR, 1992). Upakara Padudusan Alit use five “cultivars” of coconut known as